How big data and analytics reshape the wearable device market – the context of e-health. Issue 17 (2nd September 2017) - Wu, Jing; Li, He; Lin, Zhangxi; Goh, Khim-Yong
Abstract : The wearable device can be a key link between health care and big data and analytics (BDA). The benefits of BDA in health care have been widely acknowledged, but the uncertainty of the implementation of BDA has led some firms to hesitate in adopting this technology. In this research, we are keen to answer the key questions of whether the wearable device firms would adopt the BDA strategy, and how much effort they would put into it. We propose a competition model between the wearable device firms with and without BDA strategies, and consider the consumer's preference towards BDA and network effects. Our model demonstrates that the investment on BDA directly affects the firm's equilibrium price, market share and profit and at the same time, this strategy also affects the rival's performances. When the firm with BDA strategy adopts different competition strategy: conservative or expansive, the outcomes of market are different. We also find that different market structures, fully covered and partially covered, have different impacts on the firms' competition when the consumers have heterogeneous preference on BDA strategy.